Influenza vaccination during pregnancy and risk of selected major structural noncardiac birth defects, National Birth Defects Prevention Study 2006–2011. Issue 8 (22nd April 2022) - Palmsten, Kristin; Suhl, Jonathan; Conway, Kristin M.; Kharbanda, Elyse O.; Ailes, Elizabeth C.; Cragan, Janet D.; Nestoridi, Eirini; Papadopoulos, Eleni A.; Kerr, Stephen M.; Young, Sean G.; DeStefano, Frank; Romitti, Paul A.; et al.
Abstract: Purpose: To assess associations between influenza vaccination during etiologically‐relevant windows and selected major structural non‐cardiac birth defects. Study Design: We analyzed data from the National Birth Defects Prevention Study, a multisite, population‐based case–control study, for 8233 case children diagnosed with a birth defect and 4937 control children without a birth defect with delivery dates during 2006–2011. For all analyses except for neural tube defects (NTDs), we classified mothers who reported influenza vaccination 1 month before through the third pregnancy month as exposed; the exposure window for NTDs was 1 month before through the first pregnancy month. For defects with five or more exposed case children, we used logistic regression to estimate propensity score‐adjusted odds ratios (aORs) and 95% confidence intervals (CIs), adjusting for estimated delivery year and season; plurality; maternal age, race/ethnicity, smoking and alcohol use, low folate intake; and, for NTDs, folate antagonist medications. Results: There were 334 (4.1%) case and 197 (4.0%) control mothers who reported influenza vaccination from 1 month before through the third pregnancy month. Adjusted ORs ranged from 0.53 for omphalocele to 1.74 for duodenal atresia/stenosis. Most aORs (11 of 19) were ≤1 and all adjusted CIs included the null. The unadjusted CIs for two defects, hypospadias and craniosynostosis, excluded the null. These estimates were attenuated upon covariate adjustment (hypospadias aOR: 1.25 (95% CI 0.89, 1.76); craniosynostosis aOR: 1.23 (95% CI: 0.88, 1.74)). Conclusions: Results for several non‐cardiac major birth defects add to the existing evidence supporting the safety of inactivated influenza vaccination during pregnancy. Under‐reporting of vaccination may have biased estimates downward.